Peran BSI KCP Bojonegoro Suropati dalam Meningkatkan Usaha Mikro dan Menengah - Tesa Fahimatul Nurjanah; Sri Abidah Suryaningsih (Universitas Muhammadiyah Enrekang, 2022)
In developing a business requires a capital. This capital can improve and improve the condition of UMKM business actors. However, UMKM in Indonesia are currently experiencing problems with limited capital. Therefore, the role of financial institutions such as banks is needed to channel funds directly to people who need funds. UMKM business actors take financing in Islamic banks because it is a profit-sharing system and there is no interest or usury. Therefore, this study aims to determine the role of BSI KCP Bojonegoro Suropati in increasing micro and medium enterprises through murabahah financing. This study uses descriptive qualitative methods and by using primary and secondary data. Using data collection techniques of observation, interviews, and documentation. The results of this study indicate that the role of Bank Syariah Indonesia KCP Bojonegoro Suropati is to provide additional capital or financing to micro and medium enterprises in Bojonegoro Regency for working capital. After being provided with financing, micro and medium enterprises are able to increase their business with results such as increased income, expanding business, and increasing the workforce.